ZWZ-3, a Fluorescent Probe Targeting Mitochondria for Melanoma Imaging and Therapy - Liu, Zengjin; Wang, Hailan; Sun, Changzhen; He, Yuanmin; Xia, Tong; Wang, Jianv; Xiong, Xia; Zhang, Qingbi; Yang, Sijin; Liu, Li (Frontiers in Pharmacology, 2022)
The increased drug resistance and metastasis of melanoma resulted in poor prognosis of patients. Here, we designed and synthesized a novel hemicyanine-based fluorescent probe ZWZ-3, and investigated its application for melanoma imaging and treatment both in vitro and in vivo. ZWZ-3 preferentially accumulated in melanoma cells via a process that depended on the organic anion-transporting polypeptide (OATP), which targeted mitochondria on the hemicyanine cationic nitrogen. In addition, we investigated the effect and molecular mechanism of ZWZ-3 in melanoma. In vitro studies showed that ZWZ-3 promoted the generation of reactive oxygen species and induced mitochondrial-mediated cell apoptosis by upregulating Bax and activating caspase-3, caspase-9, and PARP. Importantly, ZWZ-3 also induced autophagy by upregulating LC-3II and Atg5 and downregulating P62. It significantly suppressed tumor growth of A375 xenograft tumor in mice without notable side effects. Histological and immunohistochemical analyses revealed that ZWZ-3 induced apoptosis and inhibited tumor cell proliferation. Thus, ZWZ-3 represents a novel theranostic agent that can be used to effectively targeting, detecting, and treating melanoma. It could also help monitoring disease progression and response to treatment.